Impact of obesity on operative complications and outcome after sacrocolpopexy: A systematic review and meta-analysis. (March 2021) - Wen, Qiao; Zhao, Zhiwei; Wen, Jirui; Yang, Yanlin; Wang, Ling; Wu, Jiang; Miao, Yali
Abstract: Objective: Surgery is required by many obese women with pelvic organ prolapse, and sacrocolpopexy is considered to be an effective method to correct apical prolapse. However, to the authors' knowledge, epidemiological studies have not been summarized formally. Study design: A systematic literature search of Pubmed, Medline (Ovid) and Embase databases was undertaken for articles written in English. Statistical analysis was performed using Revman 5.3. Results: In total, 7315 patients in 12 studies were included in this meta-analysis. No significant differences were found between obese women and non-obese women in terms of re-operation rate [risk ratio (RR) 1.19, 95 % confidence interval (CI) 0.88–1.59; p = 0.25], postoperative Pelvic Organ Prolapse Quantification System stage ≥2 (RR 0.86, 95 % CI 0.64–1.16; p = 0.33), transfusion rate (RR 0.91, 95 % CI 0.57–1.44; p = 0.68), mesh erosion rate (RR 1.62, 95 % CI 0.74–3.51; p = 0.23), overall rate of surgical complications (RR 1.17, 95 % CI 0.91–1.50; p = 0.23) and length of hospital stay [mean difference (MD) 0.13 days, 95 % CI −0.05 to 0.31; p = 0.15). Additionally, no differences were found in the rates of bladder injury, ileus and urinary incontinence between obese women and non-obese women. However, obese women were associated with a higher laparoconversion rate (RR 3.00, 95 % CI 1.71–5.31; p = 0.0002), higher rate of infection (RR 1.65, 95 % CI 1.25–2.20; p = 0.0005), longer operative duration (MD 14.93 min, 95 % CI 10.14–19.73; p < 0.00001) and higher estimated blood loss (MD 18.01 ml, 95 % CI 8.22–27.80; p = 0.0003) compared with non-obese women. Conclusions: The complications and curative effects of sacrocolpopexy for obese women are similar to those of non-obese women, except for the higher laparoconversion rate, higher rate of infection, longer operative duration and higher estimated blood loss in obese women. Obesity increases the operational difficulty of sacrocolpopexy to a certain extent, although it does not increase the mesh erosion rate or prolapse recurrence rate. Gynaecologists need to be aware of the possibility of the abovementioned risks when choosing sacrocolpopexy for obese patients with middle pelvic defects.